1999
DOI: 10.1007/s000130050303
|View full text |Cite
|
Sign up to set email alerts
|

On the inverse Laplace transform for C 0 -semigroups in UMD-spaces

Abstract: We prove the validity of the inverse formula of the Laplace transform for C 0 -semigroups in UMD-spaces in the strong sense and give an example which shows that the UMD-property is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…This result brings out the intimate relationship between the control theory of infinite dimensional systems and the inverse Laplace transform. However, this characterization (Proposition 3.2) of L 2 -admissibility of control operators is useful, and yields a proof of the result by [9] on the validity of the (complex) inverse Laplace transform for C 0 -semigroups in UMD-Banach spaces. In the functional analysis area, by using our approach to the characterization of admissibility, we retrieve some well-known results on incomplete and complete inverse Laplace transforms of the resolvent of a semigroup in general Banach spaces and in UMD spaces, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This result brings out the intimate relationship between the control theory of infinite dimensional systems and the inverse Laplace transform. However, this characterization (Proposition 3.2) of L 2 -admissibility of control operators is useful, and yields a proof of the result by [9] on the validity of the (complex) inverse Laplace transform for C 0 -semigroups in UMD-Banach spaces. In the functional analysis area, by using our approach to the characterization of admissibility, we retrieve some well-known results on incomplete and complete inverse Laplace transforms of the resolvent of a semigroup in general Banach spaces and in UMD spaces, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[14,Proposition 6]. Recall also that the complex inversion formula for C 0 -semigroups holds on every UMD space, see [14] or [2,Section 3.12]. In particular, it shows that there exists a generator A of a C 0 -(semi)group such that for any σ > 0 and p > 1 the following condition…”
Section: Recall That a Banach Space X Is Called A Umd Space If The Himentioning
confidence: 99%
“…As an example we can consider the shift group on X = L 1 (R), see e.g. [14,Proposition 6]. Recall also that the complex inversion formula for C 0 -semigroups holds on every UMD space, see [14] or [2,Section 3.12].…”
Section: Recall That a Banach Space X Is Called A Umd Space If The Himentioning
confidence: 99%
See 1 more Smart Citation
“…From this one can then derive the standard result on semigroups (strong convergence on the domain of the generator). Driouich and El-Mennaoui [4] showed that in case that X has the c 2008 Australian Mathematical Society 1446-7887/08 $A2.00 + 0.00 74 M. Haase [2] unconditional martingale differences (UMD) property, the convergence is strong on all of X . This was subsequently generalized from semigroups to solution families for scalar-type Volterra equations by Cioranescu and Lizama in [3].…”
Section: Introductionmentioning
confidence: 99%